Performance Properties Optimization of Triaxial Ceramic-Palm Oil Fuel Ash By Employing Taguchi Grey Relational Analysis - Zainudin, Azlan; Sia, Chee Kiong; Ong, Pauline; Narong, Oh Lai Ching; Azlan, Mohd Azwir; Lee, Woon Kiow (International Journal of Integrated Engineering, 2019)
The combustion of massive palm oil wastes has led to the production of Palm Oil Fuel Ash (POFA), especially in Malaysia. In this paper, POFA was applied in a triaxial ceramic application as a secondary filler material. Taguchi Grey Relational Analysis (TGRA) was used to distinguish new parameters efficiently. The parameters investigated were the type of POFA, composition of POFA, molding pressure, sintering temperature, and soaking time. Meanwhile, the responses analyzed included shrinkage, water absorption, apparent porosity, bulk density, and flexural strength. The experimental design was applied based on the Taguchi L18 orthogonal array after considering five parameters with 2-3 mixed levels. Statistically, sintering temperature was appointed as the most significant parameter for all responses investigated. The TGRA had suggested that the highest performances were obtained at this condition: 15 wt.% of unground POFA, pressed at 2 t, sintered at 1200 Â°C, and soaked for 300 min. The achievement of responses with optimal parameters were validated by the crystalline phase and morphology image analyses using X-ray diffraction (XRD) and scanning electron microscope (SEM) respectively.